Investigating layer-by-layer films of carbon nanotubes and nickel phthalocyanine towards diquat detection - Zattim, Cristiano A. [UNESP]; Kavazoi, Henry S. [UNESP]; Miyazaki, Celina M. [UNESP]; Alessio, Priscila [UNESP] (Springer Nature, 2024)
The indiscriminate use of pesticides makes us susceptible to the toxicity of these chemical compounds, which may be present in high quantities in our food. It is crucial to develop inexpensive and rapid methods for determining these pesticides for government control or even for the general population. In this study, we investigated the fabrication of self-assembled LbL films using multi-walled carbon nanotubes (MWCNT) and nickel tetrasulphonated phthalocyanine (NiTsPc) as an electrochemical sensor for the herbicide Diquat (DQ). The Layer-by-Layer (LbL) assembly of the (MWCNT/NiTsPc) film was examined, along with its structural and morphological characteristics. The effect of the number of layers in DQ detection was evaluated by cyclic voltammetry, followed by the detection through differential pulse voltammetry. The achieved limit of detection was 9.62 × 10−7 mol L−1. A ~ 30% decrease in sensitivity was observed in the presence of Paraquat, a banned herbicide and electrochemical interferent due to the structural similarities, which is regularly neglected in the most published studies. The sensor was tested in real samples, demonstrating a recovery of 98.5% in organic apples.
Keywords: Carbon nanotubes; Diquat; Electrochemical sensor; Multilayered materials; Nickel phthalocyanine